2013
DOI: 10.1155/2013/617243
|View full text |Cite|
|
Sign up to set email alerts
|

The Studies of Chlorogenic Acid Antitumor Mechanism by Gene Chip Detection: The Immune Pathway Gene Expression

Abstract: Persistently increasing incident of cancer in human beings has served to emphasize the importance of studies on mechanism of antitumor substances. Chlorogenic acid (CA), extracted from folium cortex eucommiae, has been confirmed to have lots of biological activities encompassing inhibition of tumor. However, the anticancer mechanism of CA remains unclear. Here, we have utilized a whole mouse genome oligo microarray (4∗44K) to analyze gene expression level of female BALB/c mice (implanted with EMT-6 sarcoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…CHL was able to inhibit metalloproteinases MMP-9 [30], microsomal glucose-6-phosphate translocase of U-87 of brain tumor-derived glioma cells [31] and inhibit proliferation of A549 human cancer cells due to the inhibitory effects on TPA-or NF-B, Activator Protein-1, and MAPK signaling [32]. Recently, the chlorogenic acid was shown to be able to inhibit tumor progression by changing gene expression involved in immune pathways [33].…”
Section: Discussionmentioning
confidence: 99%
“…CHL was able to inhibit metalloproteinases MMP-9 [30], microsomal glucose-6-phosphate translocase of U-87 of brain tumor-derived glioma cells [31] and inhibit proliferation of A549 human cancer cells due to the inhibitory effects on TPA-or NF-B, Activator Protein-1, and MAPK signaling [32]. Recently, the chlorogenic acid was shown to be able to inhibit tumor progression by changing gene expression involved in immune pathways [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ethanoic extract of mulberry leaf can induce differentiation of neuroblastoma stem cell-like population as a CSC, which is approved by down regulation of stem cell markers and up regulation of differentiation markers (Park et al, 2012). M. alba leaves contain abundant varieties of polyphenols, including chlorogenic acid, rutin, isoquercitrin, quercetin, astragalin and kaempferol (Doi et al, 2001), which are considered as strong anticancer agents (Zhou et al, 2010, Tang et al, 2010, Zheng et al, 2012, Jo et al, 2015, Kim and Choi, 2013, Naso et al, 2014, Kang et al, 2013, Amado et al, 2014. Moreover, Peter Kollar et al, showed differentiation induction of THP-1 human monocytic leukemia cells by prenyl flavonoid 4´-o-methylkuwanon E (4ME) isolated from mulberry (Kollar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid (CA), a type of depside formed by caffeic acid and quinic acid, is a polyphenolic natural compound commonly found in plants such as apples, grapes, pulp, peel, and tea leaves, especially honeysuckle and Eucommia ulmoides. 1,2 It is usually extracted from the flower buds of Lonicera confuse and folium cortex eucommiae, both of which are Chinese medical materials with important effects. CA has a wide range of biological activities including antibacterial, antiviral, antihistaminic, anti-inflammatory, analgesic, hepatoprotective, anticancer, and neuroprotective properties.…”
Section: Introductionmentioning
confidence: 99%